2008
DOI: 10.1007/s10681-008-9724-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population

Abstract: Flowering time is an important trait for the adaptation of wheat to its target environments. To identify chromosome regions associated with flowering time in wheat, a whole genome scan was conducted with five sets of field trial data on a recombinant inbred lines (RIL) population derived from the cross of spring wheat cultivars 'Nanda 2419' and 'Wangshuibai'. The identified QTLs involved seven chromosomal regions, among which QFlt.nau-1B and QFlt.nau-2B were homoeologous to QFlt.nau-1D and QFlt.nau-2D, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Many QTLs for flowering time were revealed in different regions of individual chromosomes, especially on chromosomes of groups 2 and 5 near the Ppd and Vrn genes (Lin et al 2008). In this study, the detected QTLs were found in the same chromosome regions as in previous studies (Kirwigi et al 2007;Kuchel et al 2007).…”
Section: Association Analysissupporting
confidence: 79%
“…Many QTLs for flowering time were revealed in different regions of individual chromosomes, especially on chromosomes of groups 2 and 5 near the Ppd and Vrn genes (Lin et al 2008). In this study, the detected QTLs were found in the same chromosome regions as in previous studies (Kirwigi et al 2007;Kuchel et al 2007).…”
Section: Association Analysissupporting
confidence: 79%
“…The QTL for DTH (QEet.fcu-2B) mapped to the short arm of 2B, where the photoperiod sensitivity gene Ppd-B1 is known to be located in common wheat (Mohler et al 2004) making it possible that the earliness effects contributed by PI 41025 at QEet.fcu-2B are due to allelic variation in that gene. Finally, the DTH QTL on 1B (QEet.fcu-1B) mapped near the distal end of the long arm where Lin et al (2008) detected a QTL for flowering time in common wheat thus suggesting the possibility that the 1BL QTL detected in our research is the same.…”
Section: Days To Headingmentioning
confidence: 53%
“…Interestingly, we found the epistatic interaction could be in either coupling phase or in repulsion phase, depending on the locus, suggesting that some loci are co-adapted during domestication/speciation and that loci favorable for breeding purpose may exist in both improved cultivars and landraces. In other plant species including, soybean [16,17], oilseed brassica [18] and wheat [19], epistatic control of flowering time and leaf senescence has been reported. In the near future, it is required to validate and fine-dissect the epistatic QTLs under more uniform environments such as greenhouses.…”
Section: Discussionmentioning
confidence: 99%